Graduate Attributes: Development and Testing - Penelope Little; Margaret McMillan (Halla Newcastle Education and Research Center, 2014)
Background: Universities across the world have considered which attributes were important to their graduates and examined the extent that programs included experiences and opportunities conducive to exposure to and development of the desired attributes. Methodology: An action research cycle of three phases focused on review, development and implementation of statements of curriculum intent and outcomes. Results: The iterative processes of evaluation and curriculum renewal led to agreement that graduates from university degrees should exit with attributes that distinguish their higher education experience. Conclusion: Consultative processes led to identification of Graduate Attributes (GAs) Domains unique to the University. Implementation of the GAs with a selection of programs demonstrated practicality and effectiveness.